2020
DOI: 10.1021/acssuschemeng.0c03837
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Ion Intercalation/Deintercalation of Metal Organic Framework-Derived Nanostructured NiO@C for Low-Transmittance and High-Performance Electrochromism

Abstract: Electrochromic materials hold great promise in energy-saving windows of buildings and various functional glasses. When constructing a private space, it is difficult for electrochromic materials to achieve zero transmission in the entire visible light range and achieve 100% privacy, which limits their applications in public places. In this work, a metal organic framework-derived nanostructured NiO@C film was prepared, and a green multivalent cation (Zn2+, Al3+) aqueous solution was used as the electrolyte to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…Multivalent cations (e.g., Al 3+ , Mg 2+ , Zn 2+ ) are more promising for electrochromism because they provide multiple charges compared to the monovalent Li + and H + [17][18][19][20][21][22][23]. This, as a result, will lead to a decrease in the amount of inserted cations and is expected to enhance the electrochromic performance, including rapid switching times and good cycling stability [24,25]. In addition, some of the multivalent ions are compatible with aqueous electrolytes, which shows great advantages in operational safety and low production cost [17,20,24,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivalent cations (e.g., Al 3+ , Mg 2+ , Zn 2+ ) are more promising for electrochromism because they provide multiple charges compared to the monovalent Li + and H + [17][18][19][20][21][22][23]. This, as a result, will lead to a decrease in the amount of inserted cations and is expected to enhance the electrochromic performance, including rapid switching times and good cycling stability [24,25]. In addition, some of the multivalent ions are compatible with aqueous electrolytes, which shows great advantages in operational safety and low production cost [17,20,24,26].…”
Section: Introductionmentioning
confidence: 99%
“…Among various multivalent metal ions, Zn 2+ is regarded as superior to others to trigger the electrochromism due to its simplified preparation process and nontoxicity [15,20,25,27]. Furthermore, the relatively low redox potential of Zn 2+ /Zn (−0.763 V versus standard hydrogen electrode), which shows good compatibility with pH-neutral aqueous electrolytes and thus inhibiting the occurrence of hydrogen evolution reaction [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…used a MOF‐derived large pore size NiO@C film and tested its electrochromic performance in ZnCl 2 and AlCl 3 aqueous solutions ( Figure a). [ 126 ] They found that the insertion/extraction of Zn 2+ was faster and easier than Al 3+ . The reason was believed to be that the electrostatic force between ions and the frame of Al 3+ was greater than Zn 2+ .…”
Section: Design and Improvement Of Advanced Ions‐based Electrochromic...mentioning
confidence: 99%
“…b) Ultraviolet‐visible‐near infrared transmission spectra of NiO@C film in 2M ZnCl 2 solution at 0.4 and 1 V. a,b) Reproduced with permission. [ 126 ] Copyright 2020, American Chemical Society. c) Diagram of the electrochromic battery composed of PB/Mg.…”
Section: Design and Improvement Of Advanced Ions‐based Electrochromic...mentioning
confidence: 99%
“…Unfortunately, most of them still suffer from the insufficient catalytic activity and dissatisfied long-time stability over the entire pH range, which have to be further optimized to meet the practical applications [15,16]. One effective method to solve these problems is to embed them into porous carbon doped with heteroatoms (such as N, P, and B), which can not only moderate the electronic structures and expedite the charge transfer, but also avoid the agglomeration and corrosion of active nanoparticles [17][18][19]. Furthermore, the construction of multi-phase heterostructures has provided an efficient pathway to promote the HER activity of TMP by optimizing the adsorption of intermediates and accelerating the charge transfer of heterointerfaces [20][21][22].…”
Section: Introductionmentioning
confidence: 99%